MUSCULOSKELETAL DISORDERS (MSDs) RISK ANALYSIS IN WEST SUMATERA DENTISTS AND DENTAL STUDENTS (Research report) - Abu Bakar; Valendriyani N; Elyza DG; Nadhifa S; Chusnul C (FKG Unlam, 2019)
Introduction: The prevalence of musculoskeletal complaints in dentists is high. The dental practice is assumed to have static movements, awkward, repetitive at work and requires more than 50% of the body muscles to contraction. Aim: The purpose of this study was to analyze risk factors of musculoskeletal disorders (MSDs) in West Sumatera dentists and dental students. Method: The study design was cross sectional study. There were 261 samples by total sampling technique. The instrument was Nordic Body Map (NBM) questionnaire and observation sheet BRIEF survey. Bivariate analysis used chi-square test with 95% confidence interval, α = 0.05. Results: There were correlation between work risk in right hand toward right wrist and palm right and on foot to right foot and left foot (p <0,05). There were no correlation between age, regular exercise, sleep duration and length of work toward musculoskeletal disorders complaints. Conclusion: Ergonomic interventions may have a good impact in prevention of hand/wrist complaints.